The Collective Bargaining Process - Craig, Alton (Relations industrielles / Industrial Relations, 1970)
This paper attempts to highlight the parts of the Woods 1 Report dealing with the collective bargaining process. The author discusses how the goals (inputs) of labour and management are converted to outputs via the mechanisms of collective bargaining, and gives his personal opinions on the positions advanced in the Task Force Report.1. Canadian Industrial Relations, The Report of the Task Force on Labour Relations, Ottawa, the Queen's Printer, 1969. This document will be referred to throughout this paper as the Task Force Report.